GSK‐3β inhibition suppresses instability‐induced osteolysis by a dual action on osteoblast and osteoclast differentiation. Issue 3 (28th September 2017) - Amirhosseini, Mehdi; Madsen, Rune V.; Escott, K. Jane; Bostrom, Mathias P.; Ross, F. Patrick; Fahlgren, Anna
Abstract : Currently, there are no medications available to treat aseptic loosening of orthopedic implants. Using osteoprotegerin fusion protein (OPG‐Fc), we previously blocked instability‐induced osteoclast differentiation and peri‐prosthetic osteolysis. Wnt/β‐catenin signaling, which regulates OPG secretion from osteoblasts, also modulates the bone tissue response to mechanical loading. We hypothesized that activating Wnt/β‐catenin signaling by inhibiting glycogen synthase kinase‐3β (GSK‐3β) would reduce instability‐induced bone loss through regulation of both osteoblast and osteoclast differentiation. We examined effects of GSK‐3β inhibition on regulation of RANKL and OPG in a rat model of mechanical instability‐induced peri‐implant osteolysis. The rats were treated daily with a GSK‐3β inhibitor, AR28 (20 mg/kg bw), for up to 5 days. Bone tissue and blood serum were assessed by qRT‐PCR, immunohistochemistry, and ELISA on days 3 and 5, and by micro‐CT on day 5. After 3 days of treatment with AR28, mRNA levels of β‐catenin, Runx2, Osterix, Col1α1, and ALP were increased leading to higher osteoblast numbers compared to vehicle‐treated animals. BMP‐2 and Wnt16 mRNA levels were downregulated by mechanical instability and this was rescued by GSK‐3β inhibition. Osteoclast numbers were decreased significantly after 3 days of GSK‐3β inhibition, which correlated with enhanced OPG mRNA expression. This was accompanied by decreased serum levels of TRAP5b on days 3 and 5. Treatment with AR28 upregulated osteoblast differentiation, while osteoclastogenesis was blunted, leading to increased bone mass by day 5. These data suggest that GSK‐3β inactivation suppresses osteolysis through regulating both osteoblast and osteoclast differentiation in a rat model of instability‐induced osteolysis. Abstract : Inactivation of GSK‐3β enhances bone mass through both increased osteoblast differentiation and suppressed osteoclastogenesis in an animal model for mechanical instability‐induced prosthetic loosening. Decreased osteoclast differentiation induced by GSK‐3β Inhibition, correlates to an upregulation of OPG mRNA. Blocking GSK‐3β rescues instability‐induced downregulation of Wnt16 and BMP‐2 mRNA.